Rhizospheric Flora and the Influence of Agronomic Practices on Them: A Review - Kumar, Dinesh; Shivay, Y. S.; Dhar, Shiva; Kumar, Chitranjan; Prasad, Rajendra (Proceedings of the National Academy of Sciences, India. Section B: Biological sciences, 2013)
Plants and most of the microorganisms in the rhizosphere have symbiotic relationships. While rhizodeposits (root exudates having lysates, mucilages) provide the food and influence the structure and number of microorganisms in the rhizosphere, the latter benefit the plants through secretion of a number of growth promoting hormones, organic acids and siderophores that help in increased availability and uptake of nutrients by plants. The interactions of roots and microflora may influence the plant growth positively through a variety of mechanisms, including fixation of atmospheric nitrogen by different classes of proteobacteria, increased biotic and abiotic stress tolerance imparted by the presence of endophytic microbes, and direct and indirect advantages imparted by plant growth-promoting rhizobacteria. The soil microorganisms affect plant growth, and are affected by plant growth, but there is incomplete understanding of their cumulative and interactive effects on plant performance, especially under varied crop production regimes. The diversity of cropping systems in both time and space (by rotations, intercropping, and so on) creates a mosaic of soil resources and niches, which in turn, enhances belowground biodiversity and improves the resilience of the system as a whole. Therefore, agronomic practices such as crop rotation, tillage, addition of organic manures, chemical fertilizers and mulches influence the structure and number of microorganisms in the rhizosphere. However, very little data are available on this subject. There is a need to generate such data to develop a strategy for sustainable agriculture.